Stafne bone defect of the molar region of the mandible - Mu-Hsiung Chen (Journal of Dental Sciences, 2019)
Background/purpose: The classic Stafne bone defect (SBD) is a rare small well-demarcated radiolucent lesion in the molar region of the mandible near the mandibular angle. This study reported a series of 5 SBD cases. Materials and methods: This study reviewed 4000 consecutive panoramic radiographs from February 2017 to May 2017 and found 5 classic SBD cases. The clinical and radiographic findings of these 5 SBD cases were reported. Results: We found 5 SBD cases presenting as small, well-defined, and radiolucent lesions at the typical first molar to third molar region of the mandible near the mandibular angle and below the mandibular canal. The mean age of the 5 patients at the time of diagnosis was 53.4 years (range, 45–69 years). All the 5 SBD cases occurred in male patients, 3 were on the right side and 2 were on the left side of the mandible. The mean greatest dimension of the 5 SBDs was 1.5 cm (range, 1.2–1.9 cm). All the 5 SBD cases were found incidentally on the panoramic radiographs and two of them were confirmed by cone-beam computed tomography. No surgical intervention was performed for these 5 SBD cases. Conclusion: The classic SBDs occur most frequently in male patients in the age group between 40 years and 60 years. For the SBDs at the typical site of the molar region of the mandible near the mandibular angle and below the mandibular canal, these lesions can be monitored by panoramic radiography once per one or two years. Keywords: Stafne bone defect, Mandible, Radiolucency, Panoramic radiography